Determinação simultânea de sódio, potássio, cálcio,magnésio e fósforo em biodiesel por espectrometriade emissão ótica por plasma indutivamente acopladosem preparo de amostra - Danniel Brandao Mendes (2015)
An alternative method for the simultaneous determination of sodium, potassium, calcium, magnesium and phosphorus in biodiesel its proposed, compared to the available literature, focusing on the agility of analysis. No sample preparation is carried out, and they are inserted directly into an inductively coupled plasma optical emission spectrometer (ICP OES). In addition to increasing the analytical frequency rate, the absence of pretreatment of biodiesel dramatically reduces the risk of contamination and gives greater accuracy to the method, since there is no dilution. For the quantification of analytes in commercial samples was used analytical curve prepared with methyl oleate as matrix simulacrum, as this alkyl ester is present in large amounts in biodiesel regardless their origin. Yttrium was used as internal standard to correct any effect transport. The use of methyl oleate were satisfactory for eliminating matrix effects, allowing the quantification with the calibration curve. To validate the method we used the Ministery of Agriculture (MAPA) validation guide. The accuracy was verified using two Certified Reference Materials (CRM) of 2.5 and 5.0 mg kg-1, two Reference Materials (RM) from interlaboratory tests of the Brazilian petroleum agency (ANP) and the comparison with the ABNT NBR 15553 method, and showed good agreement in all cases. Linearity (R2 0.995) and repeatability (<7%) were satisfactory on the method proposed. The detection limits (LOD) and quantification (LOQ) were determined by the use of prediction limit curve (PLC), being found LOD values of 0.12 mg kg-1, 0.16 mg kg-1, 0.23 mg kg-1 0.21 mg kg-1 and 0.24 mg kg-1, respectively for Na, K, Ca, Mg and P. The method was suitable for routine laboratory application.